Long‐term efficacy and safety of infliximab maintenance therapy in patients with plaque‐type psoriasis in real‐world practice. (1st September 2014) - Shear, N.H.; Hartmann, M.; Toledo‐Bahena, M.; Katsambas, A.; Connors, L.; Chang, Q.; Yao, R.; Nograles, K.; Popmihajlov, Z.; ,
Summary: Background: Tumour necrosis factor‐α inhibitors, including infliximab (IFX), can improve disease control of plaque‐type psoriasis. Objectives: The Real‐World Assessment of Long‐Term Infliximab Therapy for Psoriasis (REALITY) study evaluated the efficacy and safety of maintenance IFX therapy in typical clinical settings. Methods: In this prospective, observational, open‐label, multicentre study in patients with plaque‐type psoriasis, IFX 5 mg kg was infused at weeks 0, 2 and 6, and every 8 weeks thereafter during a 50‐week treatment phase. The primary outcome was ≥ 75% Psoriasis Area and Severity Index (PASI) improvement from baseline to week 50. Patients with ≥ 25% PASI improvement from baseline to the end of the treatment phase were potentially eligible to enter a 48‐week extended treatment phase. Response maintenance and other efficacy measures were evaluated. Adverse events (AEs) were collected. Results: In total 660 patients enrolled. Of 521 efficacy‐evaluable treatment phase patients (66% male, mean age 46·5 years, mean PASI 18·1), 56·8% achieved PASI 75 at the end of the treatment phase. Response was maintained at week 50 by 64·7% (205/317) of patients who achieved PASI 75 at week 14. During extended treatment, 66·3% (112/169) of patients attained PASI 75 at week 98; response was maintained at week 98 by 71·6% (101/141) of those who achieved PASI 75 at week 50. IFX was generally well tolerated. During treatment, 7·6% (50/659) of patients had serious AEs. During extended treatment, 4·1% (eight of 193) of patients had serious AEs. Conclusions: PASI 75 response was achieved by 56·8% and 66·3% of patients at weeks 50 and 98, respectively. The AE pattern was consistent with previous reports.